2008
DOI: 10.1080/00365590802022151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumour-associated symptoms on the prognosis of patients with renal cell carcinoma

Abstract: Preoperative somatic symptoms and performance status in patients with RCC provide readily available prognostic information in addition to tumour size, stage and grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In Western countries up to 40-70% of renal tumours are diagnosed incidentally [2][3][4]. Some series in the relevant literature show that conservative renal surgery provides optimal oncological control in renal tumours of less than 4 cm in diameter [2,5], and these same oncological outcomes with the use of both techniques are currently being demonstrated in neoplasms of up to 7 cm [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…In Western countries up to 40-70% of renal tumours are diagnosed incidentally [2][3][4]. Some series in the relevant literature show that conservative renal surgery provides optimal oncological control in renal tumours of less than 4 cm in diameter [2,5], and these same oncological outcomes with the use of both techniques are currently being demonstrated in neoplasms of up to 7 cm [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…Beisland et al reported an increase in the incidental detection from 21.1% in 1978-87 to 34.7% in 1988-2000 (18). Furthermore, several studies report a survival benefit of incidental detection of RCC greater than what can be explained by lower stage or grade (17)(18)(19)(20)(21)(22). Over a 40-year period, Thompson and Peek found that 75% of symptomatic patients died from renal cell carcinoma vs 15% for patients with incidental tumors (23).…”
Section: Discussionmentioning
confidence: 99%